53‐1: Invited Paper: The Winter Green and Summer Blue. Issue 1 (May 2016) - Ayama, Miyoshi; Hamano, Toshiya; Kumakura, Akihisa; Ishikawa, Tomoharu
Abstract : To investigate the best blue and green primary for color display from KANSEI‐evaluation point of view, evaluation experiment using Semantic Differential method was carried out using four different blue primaries, and five different green primaries, in Exp.1 and 2, respectively. In Exp.1, results of 430nm, 450nm, and 470nm blue primaries showed similar performance, those of 480nm blue primary showed the worst performance for almost all test images and adjective pairs. For overall, 470nm blue primary shows the best performance. In Exp.2, difference among five green primaries is less significant than that in Exp.1, while performance of 510nm is worse than other primaries. Results of both Exp.1 and 2 suggest that color appearance of objects in the image is important factor in the selection of RGB primaries.